ASPECTS REGARDING CONSUMERS' PERCEPTION OF CORPORATE SOCIAL RESPONSIBILITY IN ALBA IULIA - MAICAN, Silvia (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The main objective of the present paper is to present the way consumers in Alba Iulia, Romania, to perceive the concept of corporate social responsibility. The research represents the summary of a larger research project pretested questionnaire. In order to achieve this objective we have applied a questionnaire to a number of 51 consumers from Alba Iulia. The data were analyzed with the help of SPSS software. The paper starts with a literature review in the area of corporate social responsibility and is followed by the research methodology and the results of the research.  After analyzing the data we have reached the following conclusions: when it comes to the elements that corporate social responsibility consists of, the consumers from the mentioned area almost follow the pyramidal approach of Carroll (1999); practically, obtaining profit is largely considered to be one of the companies’ most important social responsibilities, followed by socially responsible investments, protecting the environment, etc.